2021
DOI: 10.3390/md19110644
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Water Fish Are Potential Vectors of Ciguatera Poisoning in the Gambier Islands, French Polynesia

Abstract: Ciguatera poisoning (CP) cases linked to the consumption of deep-water fish occurred in 2003 in the Gambier Islands (French Polynesia). In 2004, on the request of two local fishermen, the presence of ciguatoxins (CTXs) was examined in part of their fish catches, i.e., 22 specimens representing five deep-water fish species. Using the radioactive receptor binding assay (rRBA) and mouse bioassay (MBA), significant CTX levels were detected in seven deep-water specimens in Lutjanidae, Serranidae, and Bramidae famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 96 publications
2
8
0
Order By: Relevance
“…Conversely, LC-MS/MS proved to be more sensitive than CBA-N2a and rRBA for the detection of PbTxs in the dinoflagellate Karenia brevis [142]. Our results are also in agreement with previous studies showing that LC-MS/MS and/or CBA-N2a were more sensitive than rRBA or fRBA for the detection of CTXs in fish [87,89,127,136,143].…”
Section: Comparison Of the Performance Of The Three Detection Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…Conversely, LC-MS/MS proved to be more sensitive than CBA-N2a and rRBA for the detection of PbTxs in the dinoflagellate Karenia brevis [142]. Our results are also in agreement with previous studies showing that LC-MS/MS and/or CBA-N2a were more sensitive than rRBA or fRBA for the detection of CTXs in fish [87,89,127,136,143].…”
Section: Comparison Of the Performance Of The Three Detection Methodssupporting
confidence: 92%
“…Similar observations were reported for the detection of P-CTXs in fish from Rapa Island [89]. However, a recent study showed contradictory results, with CBA-N2a giving higher P-CTX equivalents than rRBA in three deep-water fish specimens, while no significant difference was observed between rRBA and CBA-N2a estimates for one specimen [127]. The CBA-N2a also showed a significant correlation with two immunosensing tools for the detection of P-CTXs in fish [112].…”
Section: Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…Fish are an essential nutritional and gastronomic source for the people in the Republic of Kiribati and play a vital role in subsistence and commerce. Grouper and snapper are high in nutritional and commercial value but are prohibited or restricted for sale and consumption in some areas due to their CTX accumulation capacity [ 8 ]. This study investigated the occurrence, distribution, and toxicity of high-risk ciguatera fish species (17 species groupers and snappers) from Marakei Island and Kiritimati Island of the Republic of Kiribati.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, more than 400 fish species are identified as ciguatoxic (e.g., moray eels, groupers, and snappers), and different accumulation capacities for CTXs were found among different species [ 6 , 7 ]. These toxic fish are usually bottom dwellers, and their toxicity depends mainly on their location [ 8 ].…”
Section: Introductionmentioning
confidence: 99%